Liposomal co‐delivery strategy to improve stability and antioxidant activity of trans‐resveratrol and naringenin. (5th December 2021) - Huang, Meigui; Wang, Jin; Tan, Chen; Ying, Ruifeng; Wu, Xian; Chen, Wei; Liu, Jianhua; Ahmad, Mehraj
Summary: Dietary polyphenols, viz. naringenin and trans‐resveratrol, are widely consumed by the humans. Nevertheless, being oxidation prone and highly unstable, their utilisation in food systems has been considerably limited. Here, we developed a co‐delivery liposome system to improve the storage and antioxidative stability of naringenin and trans‐resveratrol. Mean particle diameter, polydispersity index and transmission electron microscopy, of single and co‐encapsulated liposomes containing polyphenols were evaluated. Higher encapsulation efficiency was noticed in co‐loaded liposomes (RNLIP; 86.89 ± 1.75%) than liposomes separately loaded with naringenin (NLIP; 77.72 ± 2.42%) and trans‐resveratrol (RLIP; 61.98 ± 1.68%), and the effect was in an additive fashion. Co‐loaded liposomes showed the stronger environmental stability, including pH, temperature and sodium chloride than single encapsulation. In addition, co‐encapsulated liposomes exhibited higher antioxidant activity, which was evaluated by DPPH radical‐scavenging activity, ferric reducing power and lipid peroxidation inhibition ability. Therefore, these results confirmed that the strategy of co‐encapsulated trans‐resveratrol (stilbene) and naringenin (flavanone) liposome could maximise polyphenols' application in food systems.